Low-defect wide-bandgap perovskite thin film synergistically regulated by binary additives and preparation method and application thereof
Patent Information
- Application Number
- CN202611062262.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]本发明的目的在于提供一种二元添加剂协同调控的低缺陷宽带隙钙钛矿薄膜及其制备方法和应用,以克服现有技术中缺陷多、复合严重、稳定性差、添加剂不可追踪等问题
光伏与新能源领域最重要的热点问题之一是宽带隙钙钛矿材料,特别是用于叠层电池顶电池的高效稳定钙钛矿。由于钙钛矿薄膜缺陷多、结晶不可控、界面稳定性差,且缺乏可原位示踪的添加剂体系,科研人员与工程师对薄膜内部缺陷分布、钝化机制与结晶动力学并不了解。因此,他们需要花更多的时间来优化工艺、测试样品与表征分析。这不仅对实验室研发与企业生产造成时间、材料与人力成本负担,而且对高效光伏技术产业化也造成阻碍。此外,制备高质量、低缺陷、高稳定性的钙钛矿吸收层对提升电池效率与寿命、推动双碳目标实现非常重要。本发明提供一种二元协同添加剂体系,用于调控宽带隙钙钛矿薄膜、提升器件性能并实现原位监测与数据收集。目前,很多学者和研究团队都在这个领域开发了一些钝化策略与添加剂,但是本发明拥有独特的优势。例如,能够用于该领域的实验室研究与规模化生产,原因在于:
Smart Images

Figure CN122909959A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of perovskite optoelectronic device technology, specifically relating to wide-bandgap perovskite thin films, their preparation methods, and applications. Background Technology
[0002] Perovskite solar cells have become a research hotspot in the photovoltaic field due to their low fabrication cost and high photoelectric conversion efficiency. Wide-bandgap perovskite thin films can be used as the top cell in tandem solar cells, but during the crystallization process, a large number of lead vacancies, iodine vacancies, and grain boundary defects are easily generated, leading to severe nonradiative recombination and significantly reducing the open-circuit voltage and stability of the device.
[0003] Existing defect passivation strategies mostly employ single additives, making it difficult to simultaneously achieve bulk passivation, interface passivation, crystallization control, and stability improvement. Furthermore, most additives cannot be situ-tracked for distribution and action sites, hindering precise control. Therefore, developing a binary additive system capable of synergistic passivation, controllable crystallization, fluorescence tracking, and possessing both strong coordination and antioxidant capabilities is of great significance for fabricating efficient and stable wide-bandgap perovskite devices. Summary of the Invention
[0004] The purpose of this invention is to provide a low-defect, wide-bandgap perovskite thin film with synergistic regulation by binary additives, its preparation method, and its application, so as to overcome the problems of numerous defects, severe recombination, poor stability, and untraceable additives in the prior art.
[0005] This invention first provides a binary synergistic additive system, which can simultaneously achieve defect passivation, crystallization control, and interface engineering. It is also a system capable of in-situ fluorescence tracking and infrared spectroscopy identification. Because this binary synergistic additive can be designed to be compatible with existing conventional perovskite preparation processes, it is also an integrated system applicable to the photovoltaic field and optoelectronic devices. Furthermore, all additives and precursors of this invention can be prepared and used in standard solution form.
[0006] The binary synergistic additive system provided by this invention is used for defect passivation, crystallization control, and interface modification of wide-bandgap perovskite thin films; the binary synergistic additive includes a first additive, dimethylaminothioacetamide hydrochloride (DMTA) (structural formula as shown in the figure). Figure 1 As shown), the second additive is coumarin (Chromen-2-one) (structural formula as shown). Figure 2 (as shown in the figure). Among them, dimethylaminothioacetamide hydrochloride is a strong coordination passivating molecule that can form a stable coordination with lead ions, suppress uncoordinated metal defects and compensate for A-site defects; coumarin is a weak coordination interface modification molecule that can achieve surface passivation, improve carrier mobility and enhance the moisture resistance of the film.
[0007] The binary synergistic additive possesses two different passivation mechanisms: one for passivating strong coordination phases and grain boundary defects, and the other for modifying weak coordination surface and interface defects. The individual components have limited modification effects when used alone, but when combined, they produce a significant synergistic effect, achieving a synergistic effect of 1+1>2.
[0008] In the binary synergistic additive system, dimethylaminothioacetamide hydrochloride interacts with Pb through a dual site of thiocarbonyl and dimethylamino groups. 2+ Coordination can effectively slow down the crystallization rate and reduce defect formation; coumarin forms a protective layer on the film surface and achieves π-π stacking through the lactone carbonyl and aromatic ring structure.
[0009] The method for preparing low-defect, wide-bandgap perovskite thin films with synergistic regulation by binary additives provided by this invention comprises the following steps: (1) Preparation of modified precursor solution: a modified precursor solution of perovskite precursor, organic solvent and binary synergistic additive; specifically, the additive is uniformly dispersed in the perovskite precursor to form a stable and uniform modified precursor solution; wherein, the concentration, ratio and dissolution time of the additive are controlled to ensure that the film quality is stable and controllable.
[0010] (2) Preparation of perovskite thin film: The modified precursor solution is spin-coated, anti-solvent extracted and thermally annealed to form a high-quality wide-bandgap perovskite thin film; wherein, the spin-coating parameters, annealing temperature and annealing time can be controlled to make the film dense and uniform, improve the grain size and significantly reduce grain boundary defects.
[0011] Furthermore, the present invention also includes collecting, recording and analyzing the optical properties, crystal structure and photoelectric conversion properties of the thin film; including in-situ photoluminescence detection, infrared spectroscopy identification, fluorescence tracing, carrier lifetime testing and solar cell JV curve testing.
[0012] In this invention, precursor solution preparation, thin film preparation, performance testing, and data processing are used in combination to complete the entire process control and analysis from additive formulation and thin film preparation to performance characterization.
[0013] Furthermore; In step (1), the concentration of the perovskite solution is 1.4-1.7 mol / ml, the concentration of the first additive is 0.03-0.06 mol / ml, and the concentration of the second additive is 0.03-0.06 mol / ml; the concentration ratio of the perovskite precursor solution, the first additive, and the second additive is 100:(3-6):(3-6), preferably 100:3:3.
[0014] In step (1), the organic solvent is a mixture of DMSO and DMF, with a weight ratio of DMSO to DMF of (3-4):1, preferably 4:1. Ethanol is used to dissolve the hole transport layer, and IPA is used to dissolve the passivation layer.
[0015] In step (2), the perovskite layer is spin-coated using a spin coater with spin-coating parameters of 2000 r / min for 20 s and 4000 r / min for 40 s. The antisolvent is CB, added at the 40th s mark of the spin-coating process. The spin-coated device is then placed on an annealing station at a temperature of 100-110 degrees Celsius for 25-30 min. Preferably, the temperature is 100 degrees Celsius and the annealing time is 30 min.
[0016] The principle of this invention is as follows: After the binary synergistic additive is added to the precursor, dimethylaminothioacetamide hydrochloride preferentially reacts with Pb. 2+ Strong coordination regulates crystal nucleation and growth; coumarin is enriched on the film surface and grain boundaries, achieving interface passivation and hydrophobicity enhancement through weak coordination and π-π interaction; the two additives work synergistically to significantly reduce nonradiative recombination, increase photoluminescence intensity, narrow the full width at half maximum (FWHM), and stabilize the emission peak position; at the same time, the distribution and action sites of the additives can be detected and traced through infrared spectroscopy and fluorescence signals.
[0017] The low-defect, wide-bandgap perovskite thin film prepared by this invention can be used in perovskite solar cells.
[0018] This invention is directly compatible with conventional perovskite solar cell fabrication processes, requiring no complex equipment modifications. It uses low-dosage additives with significant effects, substantially improving the open-circuit voltage, short-circuit current, fill factor, and photoelectric conversion efficiency of wide-bandgap perovskite top cells, and significantly enhancing device stability in humid environments. After startup testing, the system will collect in-situ photoluminescence intensity, peak wavelength, full width at half maximum (FWHM), and absorbance data at fixed time intervals, recording and saving them in real time. Operators can directly observe the thin film crystallization process and defect passivation effects for subsequent analysis and device optimization.
[0019] Technical effects of the invention One of the most important hot topics in the photovoltaic and new energy fields is wide-bandgap perovskite materials, especially high-efficiency and stable perovskite for the top cells of tandem solar cells. Due to the numerous defects, uncontrollable crystallization, poor interface stability, and lack of in-situ traceable additive systems in perovskite films, researchers and engineers lack understanding of the internal defect distribution, passivation mechanisms, and crystallization kinetics of these films. Therefore, they need to spend more time optimizing processes, testing samples, and characterizing the films. This not only imposes a burden of time, materials, and manpower costs on laboratory research and industrial production, but also hinders the industrialization of high-efficiency photovoltaic technology. Furthermore, preparing high-quality, low-defect, and highly stable perovskite absorber layers is crucial for improving battery efficiency and lifespan, and for achieving dual-carbon goals. This invention provides a binary synergistic additive system for regulating wide-bandgap perovskite films, improving device performance, and enabling in-situ monitoring and data collection. Currently, many scholars and research teams have developed passivation strategies and additives in this field, but this invention has unique advantages. For example, it can be used for both laboratory research and large-scale production in this field because: This invention utilizes an additive system that inherently possesses infrared characteristic peaks and fluorescence signals, thus enabling site tracing and distribution detection without damaging the thin film. The additive system is fully compatible with conventional perovskite precursor solutions, spin coating processes, and annealing procedures. Therefore, no modifications to existing equipment are required, saving time and costs. Based on the synergistic passivation design of this system, it can simultaneously achieve bulk passivation, interface modification and crystallization control, and can also improve moisture resistance, making it very suitable for the preparation of high-efficiency and stable wide-bandgap perovskite solar cells. This invention features low addition amount, good repeatability, and excellent defect passivation and performance improvement effects, thereby improving the open circuit voltage, fill factor and photoelectric conversion efficiency of perovskites. Attached Figure Description
[0020] Figure 1 This is a molecular diagram of dimethylaminothioacetamide hydrochloride.
[0021] Figure 2 This is a molecular diagram of coumarin.
[0022] Figure 3 The in-situ PL peak wavelength changes over time during the crystallization process.
[0023] Figure 4 The change of the full width at half maximum (FWHM) of PL during the in-situ crystallization process over time.
[0024] Figure 5 The peak intensity during the crystallization process varies with time.
[0025] Figure 6 A 3D surface map of time-wavelength-absorbance.
[0026] Figure 7 A 2D thermogram of time-wavelength-absorbance.
[0027] Figure 8 Predict device parameters corresponding to optical thin films for QFLS devices.
[0028] Figure 9 The flowchart and structural diagram are for the preparation of perovskite.
[0029] Figure 10 The performance comparison chart shows three groups of devices: a perovskite standard device, devices using DMTA and Coumarin additives respectively, and devices using DMTA and Coumarin additives simultaneously.
[0030] Figure 11 This is a diagram illustrating the system architecture of the present invention. Detailed Implementation
[0031] This invention provides a method for preparing low-defect, wide-bandgap perovskite thin films using a binary additive synergistic regulation. The method employs a binary synergistic additive composed of dimethylaminothioacetamide hydrochloride and coumarin, along with a wide-bandgap perovskite precursor, a matching solvent, and a carrier transport layer material. Dimethylaminothioacetamide hydrochloride, as the first additive, plays a crucial role in strong coordination, oxidation resistance, and defect passivation. Coumarin, as the second additive, is used for π-conjugation regulation, interface passivation, energy level matching, and fluorescence tracing. Together, they achieve comprehensive optimization of the perovskite thin film.
[0032] The dimethylaminothioacetamide hydrochloride molecule contains a thiocarbonyl structure, which can form a strong coordination with uncoordinated lead ions in the perovskite lattice, effectively suppressing nonradiative recombination caused by metal defects. Simultaneously, the dimethylamino group in the molecule has Lewis basicity, which can compensate for perovskite A-site defects and dangling bonds on the film surface, and delay the crystallization nucleation rate of perovskite through steric hindrance, promoting uniform grain growth. Coumarin possesses an aromatic π-conjugated framework, which can enhance intermolecular π-π stacking interactions, improve film carrier mobility and interfacial electronic coupling efficiency. Its lactone structure can form a weak coordination with lead ions, achieving mild interfacial passivation. The hydrophobic aromatic ring structure can construct an interfacial protective layer, improving the film's moisture resistance. Furthermore, coumarin itself has fluorescent activity and can be used as a signal molecule for in-situ detection of additive distribution.
[0033] The preparation process of low-defect, wide-bandgap perovskite thin films is as follows: (1) Preparation of modified wide-bandgap perovskite precursor solution: Two stock solutions of additives were prepared separately: dimethylaminothioacetamide hydrochloride was dissolved in dimethylformamide to prepare a stock solution with a concentration of 0.03 mol / mL; coumarin was dissolved in a mixed solvent of dimethylformamide and chlorobenzene to prepare another stock solution with a concentration of 0.03 mol / mL; the two stock solutions were mixed in a 1:1 ratio and stirred until homogeneous to obtain a working solution of the binary synergistic additive that can be used directly.
[0034] The wide-bandgap perovskite precursor raw material was weighed according to the stoichiometric ratio and dissolved in a mixed solvent of dimethylformamide and dimethyl sulfoxide. The solution was stirred continuously until completely dissolved to obtain a homogeneous precursor solution. A prepared binary synergistic additive working solution was added to the precursor solution at a concentration of 0.03 mol / mL. The mixture was stirred continuously in the dark until homogeneous. After filtration, the modified wide-bandgap perovskite precursor solution was obtained.
[0035] (2) Fabrication of wide-bandgap perovskite solar cells (including fabrication of low-defect wide-bandgap perovskite thin films): ITO conductive glass was used as the substrate. The ITO was pretreated by sequentially using a cleaning agent, deionized water, ethanol and isopropanol for ultrasonic cleaning. After being dried with nitrogen, it was treated with ultraviolet ozone to improve the surface energy and cleanliness of the substrate.
[0036] Hole transport layers were prepared sequentially on the pretreated substrate. First, a nickel oxide nanocrystal solution was spin-coated and then thermally annealed. Next, a polyvinylcarbazole layer was spin-coated and annealed. Finally, a polyvinylpyridine thin layer was spin-coated and annealed at low temperature to complete the preparation of the hole transport layer.
[0037] The modified perovskite precursor solution was spin-coated onto the hole transport layer, and the spin-coating speed and time were controlled to ensure uniform wet film coverage. Immediately after spin-coating, the wet film was transferred to a dimethylformamide vapor atmosphere and kept there for a period of time to slow down the crystallization rate, provide sufficient time for halide ion diffusion and rearrangement, and reduce the local enrichment of bromine and chloride ions.
[0038] The film was then transferred to a hot plate for annealing, ultimately obtaining a wide-bandgap perovskite film with dense crystals, uniform composition, and low defect density.
[0039] On the prepared perovskite thin film, an electron transport layer, an electron injection layer, a buffer layer, and a metal electrode are sequentially deposited by thermal evaporation. The electron transport layer is made of C60, the buffer layer is made of BCP, and the metal electrode is made of silver, thus completing the fabrication of the optoelectronic device. The device is then tested in a nitrogen atmosphere glove box.
[0040] Furthermore, this invention employs infrared spectroscopy and fluorescence spectroscopy to identify and characterize the distribution of the perovskite thin film modified with additives.
[0041] like Figure 3 As shown, in the initial stage (0-8 s), the fluorescence wavelength rapidly redshifts. This corresponds to the evaporation of the precursor solvent, initial agglomeration of perovskite, formation of nascent crystal nuclei, and a weakening of the quantum confinement effect. In the middle stage (8-45 s), the wavelength rapidly stabilizes with only minor fluctuations. Therefore, we can conclude that the binary additive effectively stabilizes the thermodynamic process of crystallization, allowing the crystal phase to quickly reach equilibrium; it suppresses the continuous formation of disordered intermediate phases and reduces defect-type metastable crystal phases. An in-situ photoluminescence system was used to monitor the thin film crystallization kinetics in real time, recording the changes in peak emission intensity, half-width at half-maximum (HWHM), and peak wavelength over time. Combined with two-dimensional thermograms of time-wavelength-absorbance and three-dimensional surface maps, the uniformity and stability of the crystallization process were visually reflected. The results show that after regulation by the binary synergistic additive, the film's emission intensity was significantly improved, the HWHM continuously narrowed, the peak wavelength showed no significant shift, and the crystallization quality and phase stability were significantly improved.
[0042] like Figure 4 As shown, the full width at half maximum (FWHM) reflects grain uniformity and film disorder; a smaller width indicates a more uniform grain size distribution and fewer defects. In the early, slow, gradual rise stage, a large number of small nuclei emerge. In the middle, stable stage, crystal ripening occurs, with Ostwald ripening proceeding in an orderly manner. The later, slightly oscillating stage represents the final stage of crystallization. Therefore, it can be concluded that binary additives regulate the nucleation rate, avoiding instantaneous explosive nucleation (explosive nucleation easily produces fine grains and high-density grain boundaries), resulting in perovskite films with better uniformity.
[0043] like Figure 5 The fluorescence intensity shown is directly related to the degree of nonradiative recombination of the thin film; higher intensity indicates fewer defects. Additives passivate grain boundaries and bulk lead / iodine vacancies, maintaining a high fluorescence signal; this demonstrates that the binary synergistic passivation effect remains effective throughout the entire crystallization process.
[0044] like Figure 6 The perovskite film formation process shown is free of impurities and low-dimensional intermediate phases. Binary additives suppress the formation of non-perovskite impurities (lead halides, low-dimensional phases), enabling the controllable growth of pure wide-bandgap perovskite phases.
[0045] like Figure 7 The entire annealing process, as shown, exhibits a concentrated crystallization window and a single phase transition path, resulting in a highly controllable crystallization process. Coumarin also functions as a fluorescent probe, enabling in-situ visualization of the additive's effect on crystallization kinetics; DMTA provides coordination passivation, and the two work synergistically to achieve precise control.
[0046] like Figure 8 As shown, the optical PCE prediction device was used to characterize the perovskite thin film, yielding a PCE value of approximately 23%, a fill factor of 87%, an on-state voltage of 1.25V, and a current density of 21.09mA / cm2.
[0047] like Figure 9 As shown in the figure, this diagram illustrates the fabrication process of the perovskite solar cell.
[0048] like Figure 10 As shown, the perovskite solar cell with the added binary synergistic additive exhibits the best efficiency. Standard photoelectric performance tests were performed on the fabricated optoelectronic devices, current density-voltage curves were collected, and key parameters were extracted. After optimization with the binary synergistic additive, the device possesses high open-circuit voltage, high short-circuit current density, and high fill factor, achieving excellent photoelectric conversion efficiency. Simultaneously, the spectral stability, moisture resistance, and carrier transport performance of the thin film are improved, meeting the application requirements of high-efficiency, stable, and wide-bandgap perovskite optoelectronic devices.
Claims
1. A binary synergistic additive system for preparing low-defect, wide-bandgap perovskite thin films, used for defect passivation, crystallization control, and interface modification of wide-bandgap perovskite thin films; specifically comprising a first additive, dimethylaminothioacetamide hydrochloride (DMTA), and a second additive, coumarin; wherein: Dimethylaminothioacetamide hydrochloride is a strong coordination passivating molecule that can form a stable coordination with lead ions, suppress uncoordinated metal defects and compensate for A-site defects; coumarin is a weak coordination interface modification molecule that can achieve surface passivation, improve carrier mobility and enhance the moisture resistance of thin films. Dimethylaminothioacetamide hydrochloride binds to Pb via a dual-site connection between the thiocarbonyl group and the dimethylamino group. 2+ Coordination can effectively slow down the crystallization rate and reduce defect formation; coumarin forms a protective layer on the film surface and achieves π-π stacking through the lactone carbonyl and aromatic ring structure.
2. A method for preparing a low-defect, wide-bandgap perovskite thin film with synergistic regulation by binary additives, characterized in that, The specific steps are as follows: (1) Preparation of modified precursor solution: Perovskite precursor, organic solvent and binary synergistic additive are mixed and stirred to make the additive uniformly dispersed in the perovskite precursor to form a stable and uniform modified precursor solution; wherein, the concentration, ratio and dissolution time of the additive are controlled to ensure that the film quality is stable and controllable; the binary synergistic additive includes the first additive dimethylaminothioacetamide hydrochloride (DMTA) and the second additive coumarin, which are used for defect passivation, crystallization control and interface modification of wide-bandgap perovskite films. (2) Preparation of perovskite thin film: The modified precursor solution is spin-coated, anti-solvent extracted and thermally annealed to form a high-quality wide-bandgap perovskite thin film; wherein, the spin-coating parameters, annealing temperature and annealing time can be controlled to make the film dense and uniform, improve the grain size and significantly reduce grain boundary defects.
3. The preparation method according to claim 2, characterized in that, In step (1), the concentration of the perovskite solution is 1.4-1.7 mol / ml, the concentration of the first additive is 0.03-0.06 mol / ml, and the concentration of the second additive is 0.03-0.06 mol / ml; the concentration ratio of the perovskite precursor solution, the first additive, and the second additive is 100:(3-6):(3-6).
4. The preparation method according to claim 2, characterized in that, In step (1), the type of organic solvent is: the solvent for the perovskite precursor and the first and second additives is a mixed solvent of DMSO and DMF, and the ratio of DMSO to DMF is (3-4):1; the solvent for dissolving the hole transport layer is ethanol, and the solvent for dissolving the passivation layer is IPA.
5. The preparation method according to claim 2, characterized in that, In step (2), the perovskite layer is spin-coated using a spin coater with spin coating parameters of 2000 r / min for 20 s and 4000 r / min for 40 s. The antisolvent is CB, which is added at the 40th s of the spin coating process. The spin-coated device is placed on an annealing table with an annealing temperature of 100-110 degrees Celsius and an annealing time of 25-30 min.
6. A low-defect, wide-bandgap perovskite thin film obtained by the preparation method according to any one of claims 2-5.
7. The application of the low-defect wide-bandgap perovskite thin film as described in claim 6 in perovskite solar cells.